A Construção Social da Subjetividade no Contexto Acadêmico do Instituto Tecnológico da Aeronáutica - Menezes, Delano Teixeira (2007)
The Aeronautics Technology Institute (ITA) in order to prepare human resources for the upcoming demands of technological development on Aeronautics, either military or civil. Nowadays, ITA, which is also responsible for other aeronautics related fields such as engineering, has an important role in the process of national construction (nation-making). The author research the peculiarities of the social construction of subjectiveness in the academic structure of ITA., and search on how the academic structure might affect on the construction of subjectiveness of individuals, starting from their social experiences during the graduate studies. Initially the author made a origins and historical description of the ITA creation, describe politics’ and burocratics of the national military and civil organizations and the military – civilian relationship during Vargas period. Therefore, concepts of conscious discipline, integration and family are used as categories of analysis.